Real-Time Characterization of Clonal Fate Decisions in Complex Leukemia Samples by Fluorescent Genetic Barcoding - Tobias Maetzig; Anna Lieske; Nicole Dörpmund; Michael Rothe; Marc-Jens Kleppa; Violetta Dziadek; Jacob Jalil Hassan; Julia Dahlke; Dorit Borchert; Axel Schambach (Cells, 2022)
Clonal heterogeneity in acute myeloid leukemia (AML) forms the basis for treatment failure and relapse. Attempts to decipher clonal evolution and clonal competition primarily depend on deep sequencing approaches. However, this prevents the experimental confirmation of the identified disease-relevant traits on the same cell material. Here, we describe the development and application of a complex fluorescent genetic barcoding (cFGB) lentiviral vector system for the labeling and subsequent multiplex tracking of up to 48 viable AML clones by flow cytometry. This approach allowed the visualization of longitudinal changes in the in vitro growth behavior of multiplexed color-coded AML clones for up to 137 days. Functional studies of flow cytometry-enriched clones documented their stably inherited increase in competitiveness, despite the absence of growth-promoting mutations in exome sequencing data. Transplantation of aliquots of a color-coded AML cell mix into mice revealed the initial engraftment of similar clones and their subsequent differential distribution in the animals over time. Targeted RNA-sequencing of paired pre-malignant and de novo expanded clones linked gene sets associated with Myc-targets, embryonic stem cells, and RAS signaling to the foundation of clonal expansion. These results demonstrate the potency of cFGB-mediated clonal tracking for the deconvolution of verifiable driver-mechanisms underlying clonal selection in leukemia.